Biostratigraphy, chronostratigraphy and paleonvironmental reconstruction of the Palermo historical centre Quaternary succession - INCARBONA, Alessandro; Contino, A; AGATE, Mauro; Bonomo, S; Calvi, F; DI STEFANO, Enrico; GIAMMARINARO, Maria Stella; Priulla, A; SPROVIERI, Rodolfo (Italian Journal of Geosciences, 2016)
Marine deposits of the Palermo Plain were historically relevant for the Quaternary Period definition. Here we show lithostratigraphic, biostratigraphic and chronostratigraphic data collected on three boreholes in the Palermo historical centre that recovered 36.8, 42.0 and 52.0 metres of sediments overlying the Numidian Flysch. Marine sedimentary sequences span from the Calabrian Stage (calcareous nannofossil Zone MNN 19d) to the Middle Pleistocene (dominance of medium-sized gephyrocapsids within the MNN 19f Zone) and also include a short Holocene depositional event. Calcareous nannofossil, benthic and planktonic foraminifera assemblages point to a shallow coastal environment, possibly <50 m deep. This study highlights the need of a modern and reliable stratigraphic interpretation of lithotypes, to identify stratigraphic gaps and to draw deep geological structures in an area extremely vulnerable to seismic and hydrogeological hazard.